PERAN STRATEGIS KOMPONEN CADANGAN DALAM SISTEM PERTAHANAN SEMESTA INDONESIA: TANTANGAN DAN PELUANG - Estika, Febrina; Sumarno, Ari Pitoyo; Al-Mubaroq, Hikmat Zakky (Gapenas Publisher, 2024)
Indonesia, as an archipelagic country with more than 17,500 islands and a population of more than 281.6 million people, faces a variety of security challenges, including regional conflicts, terrorism, cyber threats, and natural disasters. To deal with these threat dynamics, Indonesia has adopted a comprehensive defense strategy by integrating the formation of a Reserve Component (Komcad) as mandated by Law Number 23 of 2019 concerning National Resource Management for National Defense. This research explores the importance of the strategic role, legal basis, and implementation of Komcad in the universal defense system in Indonesia. Using a qualitative methodology through a literature review approach, this study highlights the potential of Komcad in strengthening national defense through the mobilization of additional resources, civil society involvement, and increased sense of collective responsibility. The findings show that Komcad strengthens national resilience by integrating civil society expertise and encouraging inclusivity in various sectors, such as education and local communities. However, challenges remain, such as in training, coordination with the Indonesian National Army (TNI), and sustainability of funding, which require structured policies and collaborative efforts. This study concludes that Komcad has an important role in building an adaptive, effective, and inclusive defense system to deal with complex national security threats. The main recommendations include increasing public awareness, regular training, and optimizing resource allocation to increase the effectiveness of Komcad